Targeting the miR-221-222/PUMA/BAK/BAX pathway abrogates dexamethasone resistance in multiple myeloma - Zhao, Jian-Jun (Cancer Res, 2015)
Despite recent therapeutic advances that have doubled the median survival time of patients with multiple myeloma (MM), intratumor genetic heterogeneity contributes to disease progression and emergence of drug resistance. MicroRNAs (miRs), are noncoding small RNAs that play important roles in the regulation of gene expression, and have been implicated in cancer progression and drug resistance. We investigated the role of the miR-221-222 family in dexamethasone(Dex)-induced drug resistance in MM using the isogenic cell lines, MM1R and MM1S, which represent models of resistance and sensitivity, respectively. Analysis of array comparative genome hybridization (aCGH) data revealed gain of chromosome X regions at band p11.3, wherein the miR-221-222 resides, in resistant MM1R cells but not in sensitive MM1S cells. DNA copy number gains in MM1R cells were associated with increased miR-221-222 expression and downregulation of p53-upregulated modulator of apoptosis (PUMA) as a likely pro-apoptotic target. We confirmed PUMA mRNA as a direct target of miR-221-222 in MM1S and MM1R cells by both gain- and loss- of function studies. In addition, miR-221-222 treatment rendered MM1S cells resistant to Dex, whereas anti-miR-221-222 partially restored the Dex sensitivity of MM1R cells. These studies have uncovered a role for miR-221-222 in MM drug resistance, and suggest a potential therapeutic role for inhibitors of miR-221-222 binding to PUMA mRNA as a means of overcoming Dex resistance in patients. The clinical utility of this approach is predicated on the ability of anti-sense miR-221-222 to increase survival while reducing tumor burden, and is strongly supported by the metastatic propensity of MM1R cells in preclinical mouse xenograft models of MM. Moreover, our observation of increased levels of miR-221-222 with decreased PUMA expression in MM cells from patients at relapse versus untreated controls suggests an even broader role for miR-221-222 in drug resistance, and provides a rationale for the targeting of miR-221-222 as a means of improving patient outcomes.